The Routledge Guide to Teaching Translation and Interpreting Online. - Mazzei, Cristiano A., 1964-; Ibrahim Aibo, Laurence Jay-Rayon ([Place of publication not identified] : Routledge, 2022)
Routledge Guides to Teaching Translation and Interpreting is a series of practical guides to key areas of translation and interpreting for instructors, lecturers and course designers. The Routledge Guide to Teaching Translation and Interpreting Online is for educators of translation and interpreting teaching online in a variety of curricular combinations: fully online, partially online, hybrid, multimodal, or face-to-face with online components. Offering suggestions for the development of curriculum and course design in addition to online tools that can be used in skill-building activities, adaptable to specific instructional needs, this textbook is suitable for both multilingual and language-specific classes. Fully comprehensive, the book addresses the tenets and importance of process-oriented pedagogy for students of translation and interpreting; best practices in online curriculum and course design; instructor online presence; detailed illustrations of specific online assignments; the importance of regular and timely feedback; and teaching across the online T&I curriculum. Written by two experienced translators, interpreters, and scholars who have been teaching online for many years and in various settings, this book is an essential guide for all instructors of Translation and Interpreting as professional activities and academic disciplines.
Introduction by Kelly WashbourneChapter 1 - Online Translation and Interpreting EducationChapter 2 - Process-Oriented and Skill-Building PedagogyChapter 3 - Online Course DevelopmentChapter 4 - Instructor Presence in Online Courses: Synchronous and Asynchronous ConsiderationsChapter 5 - Assessment, Rubrics, AssignmentsChapter 6 - Ethics in Online Translation and Interpreting CoursesConclusion - Final ConsiderationsIndex
Keywords: Translating and interpreting -- Study and teaching; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; EDUCATION / Multicultural Education